Multi-Level Raw Material Traceability for Cinnamon Supply Chains under Aggregation and Transformation A Conceptual Model - Fauzan Aulia; Santosa; Azrifirwan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study addresses the challenge of maintaining provenance continuity in the cinnamon supply chain, where raw materials are aggregated from multiple sources and undergo various transactions and transformations. It proposes a conceptual multi-level traceability model that explicitly represents hierarchical provenance relationships, allowing for accurate tracking of raw material origins and compositions throughout the supply chain. By modeling product relationships, quantitative source contributions, and transaction histories, the approach ensures provenance and quantitative consistency even in complex scenarios involving aggregation, ownership transfers, and product changes. The model enhances supply chain transparency and quality auditability by enabling detailed reconstruction of raw material origins at each stage. Specifically tailored to the operational realities of Indonesia’s cinnamon industry, the model supports improved traceability and integrity across the spice agro-industry sector.  Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 16: Peace, Justice and Strong Institutions